Evaluating the Suitability and Potential Efficiency of Cannabis sativa Oil for Patients with Primary Burning Mouth Syndrome: A Prospective, Open-Label, Single-Arm Pilot Study. Issue 1 (30th October 2020) - Gambino, Alessio; Cabras, Marco; Panagiotakos, Evangelos; Calvo, Federico; Macciotta, Alessandra; Cafaro, Adriana; Suria, Marco; Haddad, Giorgia El; Broccoletti, Roberto; Arduino, Paolo Giacomo
Abstract: Objective: To evaluate the use of a Cannabis sativa oil in the management of patients diagnosed with primary burning mouth syndrome (BMS). Design: Prospective, open-label, single-arm pilot study. Setting: University hospital. Subjects: Seventeen patients with diagnosed BMS were included. Methods: Subjects were treated for 4 weeks with a full cannabis plant extract, which was prepared from standardized plant material (cannabis flos) in specialized pharmacies by means of Romano-Hazekamp extraction and was diluted in oil (1 g of cannabis in 10 g of olive oil). The primary outcome was the change in pain intensity (assessed by the visual analog scale, Present Pain Intensity scale, McGill Pain Questionnaire, and Oral Health Impact Profiles) at the end of the protocol and during the succeeding 24 weeks; the neuropathic pain was also investigated with a specific interview questionnaire (DN4-interview [Douleur Neuropathique en 4 Questions]). Levels of anxiety and depression were considered as secondary outcomes, together with reported adverse events due to the specified treatment. Results: Subjects showed a statistically significant improvement over time in terms of a clinical remission of the oral symptoms. Levels of anxiety and depression also changed statistically, displaying a favorable improvement. No serious reactions were detailed. None of the patients had to stop the treatment due to adverse events. Conclusions: In this pilot evaluation, the C. sativa oil provided was effective and well tolerated in patients with primary BMS. Further bigger and properly defined randomized controlled trials, with different therapeutic approaches or placebo control, are needed, however.